An Alpha-1 Antitrypsin Deficiency Screening Study in Patients with Chronic Obstructive Pulmonary Disease, Bronchiectasis, or Asthma in Turkey - Tural Onur S; Natoli A; Dreger B; Arınç S; Sarıoğlu N; Çörtük M; Karadoğan D; Şenyiğit A; Yıldız BP; Köktürk N; Argun Barıs S; Kodalak Cengiz S; et al. (International Journal of COPD, 2023)
Seda Tural Onur,1 Antonino Natoli,2 Bettina Dreger,2 Sibel Arınç,3 Nurhan Sarıoğlu,4 Mustafa Çörtük,1 Dilek Karadoğan,5 Abdurrahman Şenyiğit,6 Birsen Pınar Yıldız,1 Nurdan Köktürk,7 Serap Argun Barıs,8 Sümeyye Kodalak Cengiz,7 Mehmet Polatli9 1Department of Pulmonology, Yedikule Chest Diseases and Thoracic Surgery Education and Research Hospital, University of Health Sciences, Istanbul, Türkiye; 2Scientific and Medical Affairs, Scientific Innovation Office, Grifols, Frankfurt, Deutschland; 3Clinic of Chest Diseases, University of Health Sciences Turkey, S.B.Ü. Süreyyapaşa Chest Diseases and Thoracic Surgery Training and Research Hospital, İstanbul, Türkiye; 4Department of Pulmonology, Balıkesir University Faculty of Medicine, Pulmonology Clinic, Balıkesir, Türkiye; 5Department of Chest Diseases, Recep Tayyip Erdoğan University, School of Medicine, Rize, Türkiye; 6Department of Chest Diseases, Dicle University Faculty of Medicine Hospital, Diyarbakır, Türkiye; 7Department of Pulmonary Medicine, Gazi University, School of Medicine, Ankara, Türkiye; 8Department of Pulmonary Diseases, Faculty of Medicine, Kocaeli University, Kocaeli, Türkiye; 9Faculty of Medicine, Aydin Adnan Menderes University, Aydin, TürkiyeCorrespondence: Mehmet Polatli, Faculty of Medicine, Aydin Adnan Menderes University, Zafer Mahallesi, Efeler, Aydin, 09100, Türkiye, Email mpolatli09@gmail.comPurpose: Alpha-1 antitrypsin deficiency (AATD) is a rare hereditary condition characterized by decreased serum alpha-1 antitrypsin (AAT) levels. We aim to identify AATD in patients with chronic obstructive pulmonary disease (COPD), bronchiectasis, or asthma and to report the frequency of AAT variants in Turkey.Patients and Methods: This non-interventional, multicenter, prospective study was conducted between October 2021 and June 2022. Adult patients with COPD, bronchiectasis, asthma, liver symptoms, or family members with AATD were included. Demographic and clinical characteristics, pulmonary diagnosis, respiratory symptoms, and AAT serum levels were assessed. Whole blood samples were collected as dried blood spots, and the most common AATD mutations were simultaneously tested by allele-specific genotyping.Results: A total of 1088 patients, mainly diagnosed with COPD (92.7%) and shortness of breath (78.7%), were assessed. Fifty-one (5%) were found to have AATD mutations. Fifteen (29.4%) patients had Pi*S or Pi*Z mutations, whereas 36 (70.6%) patients carried rare alleles Pi*M malton (n=18, 35.3% of mutations), Pi*I (n=8, 16%), Pi*P lowell (n=7, 14%), Pi*M heerlen (n=2, 4%), and Pi*S iiyama (n=1, 2%). The most common heterozygous combinations were Pi*M/Z (n=12, 24%), and Pi*M/M malton (n=11, 22%). Ten patients with severe AATD due to two deficiency alleles were identified, two with the Pi*Z/Z genotype, four with the genotype Pi*M malton/M malton, three with Pi*Z/M malton, and one with Pi*Z/M heerlen.Conclusion: Our results identified AATD mutations as a genetic-based contributor to lung disease in patients with COPD or bronchiectasis and assessed their frequency in a population of Turkish patients.Keywords: alpha-1 antitrypsin deficiency, genotype, diagnosis, chronic obstructive pulmonary disease